a) x∈ (-∞;3)
b) x∈ (-∞;0] ∪ [4;+∞)
c) x∈ (-∞;0)∪(0;2/3)
d) x∈ [-1/2;1) ∪ (1;+∞)
Объяснение:
a) f(x)=√(-x+3);
-x+3≥0; -x≥-3; x≤3.
ОО: x∈(-∞;3).
b) f(x)=√(0,5x²-2x); 0,5x²-2x≥0; x(0,5x-2)≥0;
x≥0;
0,5x-2≥0; x≥2/0,5; x≥4; x∈[4;+∞);
x≤0;
0,5x-2≤0; x≤2/0,5; x≤4; x∈(-∞;0];
OO: x∈(-∞;0] ∪ [4;+∞);
c) f(x)=ln(2/x-3);
2/x-3>0; 2/x>3; x<2/3; x∈(-∞;2/3);
x≠0; x∈(-∞;0)∪(0;+∞)
OO: x∈(-∞;0)∪(0;+∞) ∩ (-∞;2/3) ⇒ x∈(-∞;0)∪(0;2/3)
d) f(x)=√(3/(x-1)+2);
3/(x-1)+2≥0; 3+2(x-1)≥0; x≥-1/2; x∈[-1/2;+∞)
x-1≠0; x≠1; x∈(-∞;1)∪(1;+∞)
OO: x∈[-1/2;+∞) ∩ (-∞;1)∪(1;+∞) ⇒ x∈[-1/2;1)∪(1;+∞)
1) 4x²-14x+6/x-3=5x+2 x неравно 3
2(2x²-7x+3)/x-3=5x+2
2(2x²-x-6x+3)/x-3=5x+2
2(x(2x-1)-3(2x-1))/x-3=5x+2
2(2x-1)(x-3)/x-3=5x+2
"x*3" сократить
2(2x-1)=5x+2
4x-2=5x+2
4x-5x=2+2
-x=4
x=-4
2) 2x²+x-28/x+4=3x-2 x неравно -4
2x²+8x-7x-28/x+4=3x-2
2x(x+4)-7(x+4)/x+4=3x-2
(x+4)(2x-7)/x+4=3x-2
"x+4" сократить
2x-7=3x-2
2x-3x=-2+7
-x=5
x=-5